Validation of a Simple Device for the Evaluation of Ankle Plantar- and Dorsi-Flexor Forces Consistent with Standard Clinical Evaluations - Giulia Rogati; Paolo Caravaggi; Andrea Martelli; Roberta Fognani; Alberto Leardini; Massimiliano Baleani (Applied Sciences, 2024)
Measuring the forces produced at the ankle joint is critical to diagnose musculoskeletal pathologies. In standard clinical practice, ankle force is often assessed through manual joint manipulation and visual observation. This study introduces a simple apparatus, the Ankle Force Transducer (AFT), based on a uniaxial load cell capable of measuring ankle forces in conditions consistent with clinical evaluations. The AFT can be placed at the extremity of any examination couch to measure ankle forces in plantarflexion and dorsiflexion. The repeatability of the AFT was assessed in 30 healthy subjects across three sessions and in two knee postures. One patient with foot-drop condition was evaluated using the same apparatus. The intra-session coefficient of variation for plantarflexion and dorsiflexion forces was around 5% and 8%, respectively. The dominant leg exhibited greater forces than the non-dominant one, and the fully extended knee resulted in significantly larger forces with respect to the flexed knee (p < 0.001). The foot-drop patient showed a 90% reduction in dorsiflexion force in the affected limb. The AFT appears to be a user-friendly tool used to measure ankle forces, which has the potential to provide more repeatable and objective measurements of ankle forces with respect to operator-dependent evaluations.